SINERGITAS GURU PENDIDIKAN AGAMA ISLAM DAN WAKA HUMAS DALAM MEMBANGUN CITRA MADRASAH : STUDI KASUS DI MTs SALAFIYAH KEREK-TUBAN - Fashi Hatul Lisaniyah; Cholifah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
To create a positive image of the madrasah, the role of public relations is very necessary, apart from that, collaboration with Islamic religious education teachers is very necessary, because Islamic religious education teachers also play a role in improving the image of the madrasah. through character building, and developing students' interests and talents, and from these two roles it can increase public trust in educational institutions. This research uses a qualitative approach with a case study type of research. Data validation uses triangulation (source triangulation, technique triangulation, and time triangulation). The synergy between Islamic religious education teachers and the head of public relations in building the image of the madrasa at MTs Salafiyah Kerek includes mutual communication and coordination. The impact of the synergy between Islamic religious education teachers and the head of public relations in building the image of the madrasa at MTs Salafiyah Kerek for the school, namely coaching and forming student character, increasing the number of students, and increasing student achievement. The impact on society is that it attracts people's interest in sending their children to MTs Salafiyah Kerek.